Analisis Kelayakan Usahatani Bawang Merah Di Kota Sukabumi - bahtiar, muhammad fadhil (Journal of Agribusiness, Social and Economic, 2025)
The agricultural sector is one of the sources of income in Indonesia, including in the field of horticulture. Shallots are one of the most widely cultivated horticultural commodities in Indonesia due to their diverse benefits. It is important to analyse the feasibility of shallot farming so that farmers can determine whether the business is feasible or not to be developed. This study aims to analyse the feasibility of shallot farming in Mina Makmur farmer group, Limusnunggal Village, Cibeureum Sub-district, Sukabumi City. The method used in this study is a survey with primary and secondary data sources. Respondents were determined by purposive method, namely farmers who received shallot seed assistance from the government. Data were analysed using farm analysis. The results showed that the R/C Ratio value was 1.55. Because the R/C Ratio value is greater than 1, shallot farming in the Mina Makmur farmer group in Limusnunggal Village is considered feasible. to be developed